Emergency Volunteer Participation in the Evolutionary Game of Public Security Governance under Community Incentives - Yuqi Yang; Liang Hong (Complexity)
The outbreak of the COVID-19 epidemic has brought profound changes to all aspects of our society and also reflects the importance of community emergency volunteers actively participating in epidemic prevention and control in the face of unexpected public security events. As a bridge between the implementation of government policies and the masses of the community, community emergency volunteers have the characteristics of high efficiency and low cost, which has a great impact on the advancement of modern social governance. In order to motivate volunteers, the community will introduce incentive mechanisms. How does the evolutionary process of a dynamic game between volunteer engagement and community motivation change? How should communities maximize the service investment of volunteers in the game process? However, the current research rarely focuses on the role of community volunteers in the modernization of Community Governance. In order to clarify this game process, this article constructs a public safety governance incentive game model consisting of communities and emergency volunteers. Based on evolutionary game theory, we obtain the evolutionary stable equilibrium point by solving the replicator dynamic equations of all parties in the dynamic system under different constraints. Finally, some numerical examples were provided to simulate the selection of agents. The research results show that the degree of community public security risk, the degree of active involvement of volunteers, the degree of inactive involvement of volunteers, and the level of community incentives have an important impact on the enthusiasm of volunteer community service investment decision-making behavior. In addition, the choice of community incentive-volunteer service investment strategy is a dynamic process, which can converge to the ideal state under certain conditions after continuous adjustment and optimization. In addition, this study puts forward suggestions and measures conducive to the game between both sides, which can provide valuable guidance for the practice of community public security governance and the improvement of government efficiency in China.